The protein and energy requirements of the South African abalone, Haliotis midae - Green, Alistair John (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2009)
The abalone (Haliotis midae) culture industry in South Africa is becoming increasingly dependent on the use of formulated feeds, due to limitations in the supply of kelp. The bulk of the feeds that are currently available were developed based on the requirements of juvenile abalone cultured within the optimal temperature range for growth (18 - 20 Â°C). However, most abalone farming facilities are land-based pump ashore operations and are thus mostly exposed to temperatures outside of this range. In addition, these feeds have been found to be unsuitable for abalone cultured at elevated water temperatures (> 20Â°C). The aim of the study was to develop size and temperature specific diets for H midoe through optimisation of dietary protein, energy and lipid levels. Abalone were cultured under farm-like conditions in three partially recirculating temperature controlled systems at either 18, 22 or 24Â°C and fed formulated diets containing graded levels of protein (18,22 and 26 %) and energy (11.6, 13.5 and 16.2 MJ.kgÂ·I ). Abalone were stocked into baskets at 5 % of available of surface area (n=36) and each diet (n=9) was fed to four baskets of abalone at each of the three temperature regimes for ten weeks. Abalone growth was temperature dependent, with growth declining from 4.33 g.month-I for abalone cultured at 18Â°C to 0.77 g.month-I at 24Â°C. Dietary protein could be reduced from 26 to 18 % provided dietary energy levels were maintained at 13.5 MJ.kg- l "¢ A dietary energy level of 11.6 MJ.kg-1 was insufficient to meet the energetic requirements of H midae regardless of the protein content of the diet. The effects of water temperature and body size on the protein requirements of H midae were investigated by culturing abalone at temperatures within the optimal range for abalone farming (i.e. 14, 16 and 18Â°C). Three size classes of abalone (15, 50 and 80 mm) were fed formulated feed containing graded levels of dietary protein (20, 26, 32, 38 and 44 %) under controlled laboratory conditions for 12 weeks, and, in a separate experiment, under commercial farm conditions for 24 weeks. It was not possible to convincingly define the optimal protein levels for abalone of different sizes in this experiment because growth rates fell below average commercial growth rates obtained on farms. Growth was temperature dependent in the laboratory trial, with the rate of weight gain of the 15 mm (ANOV A: p=0.002) and 50 mm abalone (ANOV A: p=0.02) increasing significantly with an increase in temperature from 14 to 18Â°C. In the farm trial, dietary protein content did not affect the growth rate of the 10-15 or 80 mm abalone (ANOVA: p>0.05), however, the 50 mm abalone displayed significantly higher weight gain on the 32 % (4.72Â±0.20 g.month-I ) and 38 % (5.01Â±0.34 g.month-I ) protein diets compared to those fed the 20 % protein diet (3.75Â±0.13 g.month-I ) (ANOVA: p=O.OI). Although definition of optimal dietary protein levels were not possible, the effects of dietary protein content and water temperature on the growth of H midae were independent signifying that the protein requirements of abalone are temperature independent. In addition, there was no evidence to indicate that abalone of the different sizes tested here had different dietary protein requirements. The size specific dietary lipid and protein requirements of H midae were investigated by feeding two size classes of abalone (30 and 60 mm initial shell length) diets containing graded levels of dietary lipid (4, 7, 10, 13 and 16 %) and protein (34 - 39 %) for 12 weeks. The 30 and 60 mm abalone were stocked at 7 (n=200) and 9 % (n=36) of the available basket surface area respectively and each diet was fed to four baskets of abalone of each size class. The protein requirements of H. midae are influenced by the amount of available dietary energy and thus it is possible that the ability of abalone to utilise lipids as a source of energy differs in the presence of varying levels of dietary protein. High levels of dietary lipid negatively affected the growth, condition factor and soft tissue glycogen content of both size classes of abalone. This negative effect was greater in the 30 mm size class compared to the 60 mm abalone. The corresponding increase in feed consumption and feed conversion ratio in response to increasing levels of dietary protein also provides evidence that abalone are unable to utilise dietary lipids as an energy source and high levels of dietary lipid probably inhibit the uptake of carbohydrates and protein. High dietary lipid levels did however appear to promote gonad maturation. It was possible to reduce dietary protein from 34 to 20 % without negatively affecting growth through the maintenance of dietary energy levels and thus it is recommended that future experiments on the energy content of formulated feeds should focus on the improved use of carbohydrates. Reductions in the protein portion of formulated feeds for H. midae are possible provided the diet contains sufficient levels of energy supplied from carbohydrates. As the ability of abalone to utilise dietary lipid is limited, lipids are unlikely to play a significant role as an energy source in abalone feeds. Further investigations should focus on the utilisation of various carbohydrate sources in abalone feeds.
Keywords: Haliotis midae -- South Africa; Abalone culture -- South Africa; Abalones -- Nutrition; Abalones -- Physiology